MUSEUMS OF JAPAN (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article contains information about the famous museums of Japan. The history of the origin of each museum, its exhibits, historical items are mentioned separately. Sunny country-Japan has many places where cultural recreation is possible, no matter what time of year. The collection of installations of Yayoi Kusama, the tallest Museum in the world, sculpture gardens and islands of art will captivate you.